Business Environment and Firm Performance in European Lagging Regions - Farole, Thomas; Hallak, Issam; Harasztosi, Peter; Tan, Shawn (World Bank, Washington, DC, 2017)
This paper explores the relationship between the regional business environment, lagging regions, and firm performance in four European countries: Italy, Poland, Romania, and Spain. It combines firm-level data from Orbis measuring sales, employment, productivity, and profitability, with indicators from recently completed Subnational Doing Business studies in the four countries to examine if and how the business environment is associated with firm outcomes, and whether this is mediated by being located in a lagging region. The results indicate that firms located in regions with better business environments indeed display better performance, in employment and sales growth, as well as profitability. Moreover, the paper finds evidence that being located in a lagging region aggravates the impact of a poor business environment on firm performance. The results also highlight that it matters to distinguish between regions that are "low income" (relatively poor) and those that are "low growth" (stagnating but not necessarily poor). Firm performance, the business environment, and the relationship between the two are much stronger in the latter than in the former. Overall, the results suggest that policies that improve the business environment in lagging regions would be beneficial to the performance of firms in these regions, in growth, profitability, and investment.